Sistem Informasi Disposisi Surat Pada Badan Perencanaan Pembangunan Daerah Provinsi Sulawesi Tenggara - Nadaa Qur’atul‘Ain; Syahidatul Islamiyah; Andi Juliardi Abdillah; Rizal Adi Saputra (LPPM STIKOM Tunas Bangsa, 2023)
Mail disposition information system is a web-based system of mail filing and follow-up (disposition) between employees within the scope of an office. This system has been created to solve administrative problems managing mail archives and following up on incoming mail. The design process for the development of this letter disposition system used the Waterfall method. The system that has been built has been tested using blackbox testing with the result that all the features of the mail disposition system can run perfectly. The Research of the letter disposition system is expected to assist in managing the storage and searching of letter archives as well as follow-up at the Badan Perencanaan Pembangunan Daerah in Southeast Sulawesi Province, Indonesia.